Pengaruh Gaya Hidup (Life Style) dan Harga Harga Terhadap Keputusan Pembelian Pada Kantin Yuank Kota Bima - Khairul Anas; Muhajirin Muhajirin (Journal of Business and Economics Research (JBE), 2020)
The purpose of this study is to determine whether there is an influence of lifestyle (life style) and price on purchasing decisions in the city of Bima's Yuank canteen. This type of research is associative. This research was conducted in the Yuank Canteen in Bima City. The population in this study are all consumers who buy food and drink in the Yuank cafeteria. The sampling technique used by researchers is acidental sampling and obtained a sample of 96 people. Data collection using questionnaires. The variable results show that lifestyle and price variables influence the purchasing decisions of Bima's Yuank Canteen. By looking at simple linear regression analysis of lifestyle variables (life style) on purchasing decisions and t tests. It can be seen that the coefficient of the price variable has an influence on the purchasing decision of Bima's Yuank Canteen next to 0.435, and the lifestyle variable is 0.367 where the coefficient of determination shows the value of 23.6% while the ratio of 76.4% is explained by other variables. And the results of this study indicate that lifestyle (life style) and price both have an influence on purchasing decisions at Bima's Yuank canteen